Etika Relasional Dakwah dalam Tafsir Al-Misbah - Siti Robiah Adawiyah; Awaluddin Pimay; Mohamad Arja Imroni (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
This article examines the relational ethics of da'wah in M. Quraish Shihab's Tafsir Al-Misbah, highlighting the shift from normative da'wah toward a humanistic and non-dominative approach. Da'wah is often practiced as a one-way transmission of truth that positions the mad'u (the recipient of da'wah) as an object. This study departs from the assumption that Tafsir Al-Misbah offers a different model, namely da'wah as a relational practice that respects human dignity and opens space for dialogue. This research is based on literature with a thematic approach to examining the verses of the Prophet Muhammad's preaching in the interpretation of Al-Mishbah.Data sources consist of da'wah verses as primary data and da'wah literature, thematic interpretations, and previous research as secondary data. The research aims to identify the principles of relational ethics in the interpretation of da'wah verses and their relevance in pluralistic societies. The analysis employs a framework of relational ethics synthesized from Emmanuel Levinas's thought on responsibility toward the Other and Fahruddin Faiz's concept of humans as both relational beings and servants ('abd). This synthesis positions da'wah as an ethical relation that prioritizes respect for alterity, empathy, and moral responsibility before claims to truth. The findings show that Tafsir Al-Misbah positions da'wah as ethical communication that rejects coercion and prioritizes wisdom, compassionate advice, and dialogue. This approach constructs a da'wah model that is humanistic, inclusive, and non-coercive, placing transformation as the outcome of ethical relations between subjects. Within this framework, da'wah emerges as a relational practice relevant to pluralistic and complex societies.